Perancangan Website Sebagai Media Promosi Digital Pada UMKM Ladu Arai Pinang One - Ulfa Ramadhani; Rizka Apriani Putri; Nacwa Tipani HN; Sularno .; Novadilastri . (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Advancements in information technology have significantly impacted various business sectors, including Micro, Small, and Medium Enterprises (MSMEs). One way technology can support MSME growth is through the use of websites for digital promotion and marketing. This article describes the website design process for the MSME "Ladu/Arai Pinang One," conducted as part of a Project-Based Learning (PBL) initiative within the Business Administration Study Program at Padang State Polytechnic. A descriptive method was employed, utilizing a Project-Based Learning approach that involved observation, interviews, and documentation regarding the MSME's operations. The results indicate that prior to the website's creation, product promotion was limited to simple methods such as WhatsApp and word-of-mouth resulting in a restricted market reach. The designed website serves as a platform for sharing business profiles, product details, and ordering information, while also enhancing the MSME's professional image. Furthermore, the website is expected to expand market reach, boost consumer trust, and assist the MSME in adapting to digital technology trends. Implementing a website for promotion represents a strategic step toward digital transformation, thereby strengthening the business's competitiveness in the digital era.